(untitled) (SAARC Journal of Agriculture, 2020)
Now-a-days, the poultry production in Bangladesh has become a sustainable and profitable industry. The poultry sectors are contributing to meet the national demand of proteins as well as implementing food security along with employment generation. The poultry industries are frequently affected by respiratory diseases. There are five viral respiratory diseases associated with respiratory systems such as Avian influenza (AI), Newcastle disease (ND), Infectious bronchitis (IB), Infectious laryngotracheitis (ILT), and Avian metapneumovirus (AE). Among them, AI outbreaks have been occurring regularly with changing genetic characters since 2007 and atotal of 556 AI outbreaks have been reported yet in Bangladesh that placed in most AI reporter countries. Bacterial diseases like Mycoplasmosis, Ornithobacterium rhinotracheale, Fowl cholera, and Infectious coryza are mostly prevalent respiratory diseases in Bangladesh. Mycoplasmosis is become a major threat for poultry industry especially Sonali (a cross-bred) type chickens due to poor biosecurity and breeding management. With respect to fungal diseases, Aspergillosis or brooder pneumonia is a highly prevalent respiratory disease in Bangladesh with causing pneumonia in young chickens. However, respiratory diseases are prevalent in higher rates and cause outbreaks frequently. SAARC J. Agri., 18(1): 1-11(2020)